POTENSI DAN PEMANFAATAN LIMBAH SUSU BUBUK UNTUK FORTIFIKASI KOMPOS PADA PERTANIAN SAYUR ORGANIK - Suselo Harjo; Akhmad A. Amin; Syaiful Anwar (Journal of Natural Resources and Environmental Management, 2015)
Composting can be use as one of the alternatives solution to managing solid waste. The purposes of this research are (1) Knowing the initial description of the potential milk powder and waste management through surveys (2) Knowing the influence of the concentration of Waste Water Treatment Process (WWTP) sludge as waste decomposers and fortification dose of milk powder. Indicators used are compost quality, yield and growth of leafy vegetables and improvement of soil fertility. This research used 2 factors and 3 replications. Factor A: WWTP sludge concentrations (0%, 10% and 20%) and Factor B: dose fortification of milk wastes powder (0%, 10% , 20% and 30%). Complete factorial designs were used as a tools in this research. The survey shows that the average distributor waste is 2,35% per month. Waste management of milk powder solid waste usually done by burn it with diesel fuel or gasoline. In the industries 68,7% of waste are damaged waste that burn in incinerator. In the quality of compost show that interaction between A and B havehighly significant effect in total of N. The result of fortified compost has met quality standards microbe well as heavy metals. The aplication of fortified compost was increase soil labile C organic. Factor B have significant effect in the width of leaves and yield of vegetable. In the soil fertility show that the interaction between A and B have significant effect in total of Nand K2O .The best combination in this research is A3B4 (20 % WWTP sludge and dosage fortification solid waste 30%dry basis).